The in vitro anticancer effects of FS48 from salivary glands of Xenopsylla cheopis on NCI-H460 cells via its blockage of voltage-gated K+ channels - Xiong Weichen; Fan Huizhen; Zeng Qingye; Deng Zhenhui; Li Guanhui; Lu Wancheng; Zhang Bei; Lai Shian; Chen Xin; Xu Xueqing (Acta Pharmaceutica, 2023)
Voltage-gated K+ (Kv) channels play a role in the cellular processes of various cancer cells, including lung cancer cells. We previously identified and reported a salivary protein from the Xenopsylla cheopis, FS48, which exhibited inhibitory activity against Kv1.1-1.3 channels when assayed in HEK 293T cells. However, whether FS48 has an inhibitory effect on cancer cells expressing Kv channels is unclear. The present study aims to reveal the effects of FS48 on the Kv channels and the NCI-H460 human lung cancer cells through patch clamp, MTT, wound healing, transwell, gelatinase zymography, qRT-PCR and WB assays. The results demonstrated that FS48 can be effective in suppressing the Kv currents, migration, and invasion of NCI-H460 cells in a dose-dependent manner, despite the failure to inhibit the proliferation. Moreover, the expression of Kv1.1 and Kv1.3 mRNA and protein were found to be significantly reduced. Finally, FS48 decreases the mRNA level of MMP-9 while increasing TIMP-1 mRNA level. The present study highlights for the first time that blood-sucking arthropod saliva-derived protein can inhibit the physiological activities of tumour cells via the Kv channels. Furthermore, FS48 can be taken as a hit compound against the tumour cells expressing Kv channels.